Bluegrass Bluesman : A Memoir - Graves, Josh (Book collections on Project MUSE., 2012)
A pivotal member of the hugely successful bluegrass band Flatt and Scruggs and the Foggy Mountain Boys, dobro pioneer Josh Graves (1927-2006) was a living link between bluegrass music and the blues. In this book, the influential performer shares the story of his lifelong career in music.